Altarnum An entrance to the concept، tools and value - ALazamat, Huseen; ALshentawe, Mouneer (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study tried to stand on the phenomenon of Altarnum، performance، as reflected in this phenomenon، how to perform text linguistic and linguistic diversity of the means، which may be the satiation of an articulation or subsequent prolongation or modifying and deletion. The study concluded that Altarnum is a kind of audible performance which is dominant in poetry. It is based on prolongation a and rewind، to achieve homonymy during the long tidal articulation or the use of suffix often Al- Tanween، Altarnum، is not limited to the Tanween of Altarnum، but achieved in some types of diversity in other kinds of Al-Tanween. In Altarnum، using Al-Tanween is legal even if it contradicts with other grammarians' opinions، because of Nun's value rhythmic grainy، and systematic musical frequencies. The study also concluded that Altarnum which is different from Solomon(chanting)، which is nothing more than raising the voice without homonymy، which seems to replace the "Maddah" with "Noan" or bind the end of speech Soothing.